Effect of gamma radiation on elastic and optical properties of Tm₂O₃/CeO₂-doped zinc borotellurite glass system - Laoding, Hasnimulyati (2017)
Two series of zinc borotellurite glasses that were doped with thulium and cerium oxide were successfully fabricated using the known melt-quenching technique. The glasses were prepared based on the empirical formula of {[(TeO2)0.7(B2O3)0.3]0.7[ZnO]0.3}1-x{Tm2O3/CeO2}x with the concentration of the rare earth oxides were varied from 0.00 to 0.05 mol. The structural, elastic and optical properties of the glass samples were tested using densimeter, Fourier Transform Infrared Spectrometer (FTIR), X-ray diffraction (XRD) analysis, ultrasound technique and UV-Visible Spectrophotometer (UV-VIS). The samples with 1 mol% of dopants were exposed to gamma radiation with dose ranging from 10 to 35 kGy and all the tests were done before and after the radiation process. As the rare earth oxides were added into the glass system, the density of the glass was found to increase from 3.69 to 4.99 g/cm3. Meanwhile, the molar volume (Vm) of glass decreases rapidly at 0.01 mol of the additional oxide and varies beyond that. The minimum and maximum values for Vm are 25.57 and 31.75 cm3/mol respectively. In terms of FTIR spectra, the absence of Zn-O, Tm-O and Ce-O bonds implies that these bonds have been broken and these oxides take the role as network modifier by filling up the interstitial spaces inside the glass network. The amorphous nature of the glass is confirmed using XRD analysis. Besides, the elastic moduli and other elastic parameters of the glass under study generally found to increase with the substitution of Tm2O3 and CeO2 while the value of Poisson’s ratio lies in the range of 0.2633 to 0.2740. In terms of optical parameters, all of them exhibit some variations as the dopants are added. After the glass samples with 1 mol% of rare earth oxides is radiated with gamma rays, the density for Ce-doped glass found to decrease from 4.600 to 3.576 g/cm3 whereas for Tm-doped glass, it varies with minimum value of 4.57 g/cm3 and maximum value of 4.66 g/cm3. Meanwhile, the molar volume for both glass series is totally opposite to density. The glass samples also maintain their amorphous nature after radiation even though new absorption bands were found to be produce in the FTIR analysis. The elastic moduli for cerium doped glass show a decrement after exposed to gamma rays while in thulium doped glass, they show an increasing trend. Furthermore, the optical band gaps for both glass series tend to decrease with the increment of radiation dose. In conclusion, the addition of thulium and cerium oxide into zinc borotellurite glass found to alter the glasses’ properties differently. In addition, the effects of gamma radiation also are different for both glass series. This research can contribute new knowledge regarding rare-earth doped zinc borotellurite glass and the effect of gamma radiation on them. Besides that, these glasses also have a high potential to be used as gain media in laser devices for medical surgery and as fibre amplifier in radiation-exposed environment.